2004
DOI: 10.1037/0882-7974.19.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Part-Set Cuing Effects in Younger and Older Adults.

Abstract: In 3 experiments, the authors examined part-set cuing effects in younger and older adults. Participants heard lists of category exemplars and later recalled them. Recall was uncued or cued with a subset of studied items. In Experiment 1, participants were cued with some of the category names, and they remembered fewer never-cued categories than a free-recall condition. In Experiment 2, a similar effect was observed for category exemplar cues. There was also an age difference: By some measures, a small number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 50 publications
3
24
1
Order By: Relevance
“…Zacks et al (1996) reported evidence that older adults show impaired directed forgetting, whereas Moulin et al (2002) found robust retrieval-induced forgetting and Marsh, Dolan, Balota, and Roediger (2004) found robust part-list cuing in the elderly. Together with the present results on children's episodic recall, these findings on older adults' episodic recall indicate that retrieval-induced forgetting and part-list cuing develop early in life and remain intact for the greater part of the lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Zacks et al (1996) reported evidence that older adults show impaired directed forgetting, whereas Moulin et al (2002) found robust retrieval-induced forgetting and Marsh, Dolan, Balota, and Roediger (2004) found robust part-list cuing in the elderly. Together with the present results on children's episodic recall, these findings on older adults' episodic recall indicate that retrieval-induced forgetting and part-list cuing develop early in life and remain intact for the greater part of the lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments 2 and 3 demonstrate that this unintentional automatic inhibition appears early in childhood and remains intact for the greater part of the adult lifespan (e.g., Marsh, Dolan, Balota, & Roediger, 2004, for whole-word cuing effects in the elderly).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the apparent retrieval benefit observed in the SC conditions is that the presentation of images for a subset of events may have rendered the remainder of the events more difficult to recall. Part-set cueing is a form of retrieval-induced forgetting that has been observed in both younger and older adults (Marsh, Dolan, Balota, & Roediger, 2004). In typical part-set cueing procedures, participants study a list of items (e.g.…”
Section: Autobiographical Recallmentioning
confidence: 99%